Adan laundry / Noor Ammirrah Md Uzir, Noor Atika Ab Wahab and Siti Rofilah Ismail - Md Uzir, Noor Ammirrah; Ab Wahab, Noor Atika; Ismail, Siti Rofilah
This case study involves the Adan Laundry Puncak Alam which offers self-services laundry. It provides of full facilities such as detergent, lagoon wet cleaning system, normal wash laundry system, and professional steam ironing. Adan Laundry becomes popular among parents and children during the weekend. This business located in strategic location in Pusat Niaga Astana Alam, Puncak Alam which is close to UITM Puncak Alam. The distance of Adan Laundry is about 7.3 kilometres from the UITM Puncak Alam which is takes about 11 minutes to get there. The target market of the business is students UITM Puncak Alam. Furthermore, there are UlTM's students that rent in the Saujana Utama residential area. Thus, during the weekend, the Adan Laundry will become the target place to the students. Thus, this study is going to analyse the problem to offer the solution to Adan Laundry services